БИЛИМЛЕНДИРИЎ СИСТЕМАСЫНДА ИННОВАЦИЯЛАРДЫ ЕНГИЗИЎДЕ ИНФОРМАЦИОН ТЕХНОЛОГИЯЛАРДЫҢ РОЛИ - Ескараев, Т. (SCIENCE and SOCIETY, 2024)
The article deals with the role of introducing innovations into the subject of teaching information technology in higher educational institutions and their significance.